A Systematic Literature Review on Artificial Intelligence Features Driving Purchase Intention on Web Commerce: Insights into Customer Experience and Trust Using Python-Based Analysis - Siska Erliana (Universitas Negeri Surabaya, 2025)
This study presents a Systematic Literature Review (SLR) exploring how artificial intelligence (AI) features influence purchase intention on web commerce platforms, with a focus on customer experience and trust as mediating factors. Using Python-based bibliometric and text mining tools, the review examines academic literature published between 2017 and 2024. Findings suggest that AI features such as personalization, chatbots, recommendation systems, and virtual try-ons significantly contribute to enhancing user experience and building trust, which in turn foster purchase intention. The study also highlights methodological trends and proposes directions for future research.